THE EFFECT OF ARABICA AND ROBUSTA COFFEE BLENDS ON CAFFEINE CONTENT, ACIDITY AND ORGANOLEPTIC PROPERTIES OF INSTANT COFFEE - Tineke M Langi; Frangky Jessy Paat; Samuel D. A. Kusuma; Yoakhim Y.E. Oessoe; Suzanne L. Liwu; Christine F Mamuaja; Luther A. Latumakulita; Dedie Tooy; David P Rumambi; Herry F Pinatik; Rinny Mamarimbing (Journal of Agriculture, 2023)
One of the types of coffee in Indonesia that can be processed into instant coffee is Gayo coffee. This research was conducted to find out the quality of instant coffee brewed in a mixture of arabica and robusta Gayo coffee. The method used in this research is a complete randomized design method (RAL) consisting of five treatments of a mixture of arabica coffee and robusta Gayo by making observations on acidity levels (pH), caffeine levels, and organoleptic of instant coffee brewing. The results showed that the mixed instant coffee types of Arabica and Robusta Gayo from each formulation produced different levels of acidity with a pH value of 5.55 – 6.43 and a different caffeine concentration with a value of 2.79% - 3.27% and qualified the quality requirements of the 2014 Indonesian National Standard (SNI) with a caffeine concentration value above a minimum of 2.5%. The brewing taste favored by the panelists was Gayo instant coffee, a mixture of 50% Arabica: 50% Robusta with a mild sour and bitter taste, a pH value of 5.94, and a caffeine content of 3.19%. The color and aroma of the coffee brewing favored by the panelists was Gayo instant coffee, a mixture of 70% arabica: 30% robusta with the quality of the brewing color of dark chocolate, the aroma of a little spice, the pH value of 5.55 , and the caffeine content of 2.79%.